Study of Soil Quality (Moisture and pH) Upon the Growth of Okra Plant Using IoT Technique - Mohd Ridhuan, Amir Umar; Abd Rahman, Ramhuzaini (Research Progress in Mechanical and Manufacturing Engineering, 2022)
The Internet of Things (IoT) is an evolving platform integrating numerous technologies from various fields. For this study, the aim is to implement IoT in the agriculture sector, specifically in monitoring the soil quality upon the growth of the okra plant. The system’s design consists of a web-based system, a monitoring system for agriculture, and a communication network. This system is designed to allow the monitoring process of soil quality through mobile phones. The micro-controller that is used to process the data from the sensors is NodeMCU. The micro-controller is programmed using Arduino IDE software to receive the reading from the sensors, process the data, and send it to a mobile phone via an application called Blynk. The ideal value for soil moisture is between 50% to 70%, while for the soil pH value, the range more to the acidic side, which is between 5.0 to 7.5. After experimenting and monitoring for seven days, the results show that the height of the okra plant has increased from 6 cm to 9 cm. The positive output results from controlling and monitoring the parameters, soil moisture and soil pH between the ideal value for seven days. This system is essential to facilitate farmers in managing the crops while increasing the production rate of fresh okra vegetables.